The navigator - Crisp, Donald, 1880-1974; Keaton, Buster, 1895-1966; McGuire, Kathryn, 1897-1978; Metro-Goldwyn-Mayer Pictures; Cinetel Films ([Beverly Hills, CA] : Metro-Goldwyn Pictures Corp., 1924)
"The navigator follows the comic and romantic mishaps that ensure when a pair of pampered youths are set adrift on a ship marked for destruction. Buster's comic timing was never better, but no scene is as amazing as the revolutionary deep sea diving sequence.
"A Metro-Goldwyn attraction."
Buster Keaton, Kathryn McGuire, Frederick Vroom.
Cinematographers, Elgin Lessley and Byron Houck.
Silent, with English intertitles and musical accompaniment; Spanish subtitles.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 14, 2015)
Keywords: Beaufort (Ship); Steamboats -- Drama; Deep diving -- Drama; Cannibalism -- Drama; Submarines (Ships) -- Drama; Oceania -- Drama; Silent films; Slapstick comedy films; Feature films; Internet videos; Streaming video